1999
DOI: 10.1002/etc.5620180814
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and desorption rate comparisons for 1,2‐dichlorobenzene to a peat soil

Abstract: Abstract-The rates of sorption and desorption were quantified for 1,2-dichlorobenzene to and from a peat soil using a batch methodology. Solute-sorbent contact times of 2, 7, 14, 49, and 99 d were studied for the desorption rate experiments. The experimental data were simulated using a distributed rate parameter model. The optimal model fitting parameters and their 95% confidence intervals were computed. The rates of desorption were significantly slower than the rate of uptake for solute-sorbent contact times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…In one of the experiments, desorption time was extended to more than 4,000 h to assess whether the very‐slow‐desorption rate constant would change with extended desorption times. Although use of two‐ or three‐compartment models has been questioned [23], our findings showed that the very‐slow‐desorption rate constant was, indeed, constant for these desorption times. For the time interval between 1,000 and 4,000 h of purging, the decrease of ln( M t / M o ) was linear with time (the r 2 values of the linear regressions were 0.98 and 0.96 for the duplicate experiments).…”
Section: Resultsmentioning
confidence: 58%
“…In one of the experiments, desorption time was extended to more than 4,000 h to assess whether the very‐slow‐desorption rate constant would change with extended desorption times. Although use of two‐ or three‐compartment models has been questioned [23], our findings showed that the very‐slow‐desorption rate constant was, indeed, constant for these desorption times. For the time interval between 1,000 and 4,000 h of purging, the decrease of ln( M t / M o ) was linear with time (the r 2 values of the linear regressions were 0.98 and 0.96 for the duplicate experiments).…”
Section: Resultsmentioning
confidence: 58%
“…Typically, sorption experiments are performed to evaluate solid/liquid distribution coefficients. Sorption experiments alone cannot predict desorption behavior, because hysteresis and irreversibility commonly occur to various degrees (11,15,(33)(34)(35). Some investigators have conducted desorption experiments in an attempt to quantify the effects of desorption on mineralization of sorbed chemicals (10,66).…”
mentioning
confidence: 99%
“… Cumulative distribution functions for the gamma distributions of linear‐driving‐force rate coefficients describing sorption of 1,2‐dichlorobenzene onto four natural sorbents. These are the best‐fit gamma distributions as determined by Deitsch and coworkers [9,26,27]. Table 2 shows the corresponding shape factors and scale factors.…”
Section: Application To Experimental Datamentioning
confidence: 86%
“…In previous publications, Deitsch and coworkers [9,26,27] examined the sorption and desorption of DCB by five natural sorbents: Woodburn silty sand, Picatinny sand, Picatinny peat, Army Corps of Engineers (ACE) sand, and ACE silty clay.…”
Section: Application To Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation